The Impact of Financial Development and Globalisation on Economic Growth: Evidence from a Macro Panel of Ten Countries - Fuinhas, José Alberto; Marques, António Cardoso; Lopes, Cátia (Asian Economic and Financial Review, 2019)
This paper examines the impact of financial market development and globalisation on economic growth in ten countries (Argentina, China (Hong Kong SAR), Israel, Japan, Malaysia, Mexico, Singapore, Switzerland, United States and South Africa) from 1980 to 2015. To perform the investigation two aspects of financial market development, i.e. the banking sector and the stock market were focused on. The study benefited by the fact that in 2018 the KOF Globalization Index was substantially upgraded, disclosing de facto andde jure measures. An ARDL bounds test approach was used to examine the short- and long-term properties of those relationships. The results point to banking sector development impacting economic growth both in the short- and long-term. The stock market development impacts economic growth in the long-term. The 2018 upgraded KOF Globalization Index indicators de facto and de jure have been demonstrated to be statistically significant. The forms of globalisation more significant in the model are political globalisation, de jure, in the long-term and financial globalisation, de facto, in the short-term. The speed of adjustment of the panel is negative and statistically highly significant, supporting the evidence of long memory/cointegration in the relationship between financial market development, globalisation and economic growth. Policies that promote banking sector development should be implemented to promote economic growth. There should be sound regulation of the banking system promoted and confidence instilled in the banking markets so that resources can be effectively mobilised to increase the economies’ productivity.